Determining cultural implication content analysis of Pinoybaiting youtube videos - Baltazar, Sophia Marie C. (Lagom: Compendium of CAS Undergraduate Research Abstracts, 2021)
"Pinoybaiting" was first coined by Filipino content creator MA Buendia to describe an exploitative marketing strategy by foreign content creators that utilities aspects of Philippine culture to bait Filipinos into interacting with their content. Given the specific literature gap on Filipino representations in foreign media, studying Filipino culture as presented in Pinoybaiting videos provides insights on how Filipinoa are understood and presented through the eyes of foreigners. Additionally, it is a relevant phenomenon to study because it is a cross-cultural interaction that takes place on one ofthe most popular social media platforms in the Philippines: Youtube.